The view from Saturday - Konigsburg, E. L. (New York Aladdin Paperbacks, 1998)
Four students, with their own individual stories, develop a special bond and attract the attention of their teacher, a paraplegic, who chooses them to represent their sixth-grade class in the Academic Bowl competition.
"A Jean Karl book."
"Aladdin Newbery"--Spine.
Keywords: Teacher-student relationships -- Fiction; Friendship -- Fiction; Schools -- Fiction; Contests -- Fiction; Physically handicapped -- Fiction